Evaluation of antibacterial preparations on growth rate and feed efficiency of young pigs - Allee, G.L.; Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety-six young pigs were used to evaluate various antibacterial preparations on rate and efficiency of gain. Each of the antibacterial preparations increased rate of gain over pigs fed the non-medicated basal diet. There were no significant differences in daily gains of pigs fed ASP-250, CSP-250, Lincomix, Mecadox, or Stafac.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Antibacterial preparations; Growth rate; Feed efficiency; Daily gain